Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3171/ped.2005.103.2.0131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic-impregnated shunt catheters in decreasing the incidence of shunt infection in the treatment of hydrocephalus

Abstract: The AIS catheter significantly reduced incidence of CSF shunt infection in children with hydrocephalus during the early postoperative period (< 6 months). The AIS system used is an effective instrument to prevent perioperative colonization of CSF shunt components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 48 publications
2
55
1
3
Order By: Relevance
“…There is evidence that antibiotic-impregnated catheters can reduce the incidence of meningitis in adult patients with EVDs, 24 and this information has been extrapolated to pediatric patients in many centers. There is weak evidence that antibiotic-impregnated catheters can reduce the rate of shunt infection, 8,17,23 although the results are mixed. 10,19 An ongoing study of a shunt surgery infection protocol has initial promising results, and is one of the many strategies that are needed to reduce the incidence of shunt infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that antibiotic-impregnated catheters can reduce the incidence of meningitis in adult patients with EVDs, 24 and this information has been extrapolated to pediatric patients in many centers. There is weak evidence that antibiotic-impregnated catheters can reduce the rate of shunt infection, 8,17,23 although the results are mixed. 10,19 An ongoing study of a shunt surgery infection protocol has initial promising results, and is one of the many strategies that are needed to reduce the incidence of shunt infection.…”
Section: Discussionmentioning
confidence: 99%
“…Total shunt revision in our series represented 58.1% of shunt procedures which is much higher than the result of Naftel et Shunt-related infections represent 2 to 27% of total shunt procedures (8,15,18,21,22,28,27,30). Shunt revision due to shunt related infection in our study represented 11.22% of the total cases which is slightly higher than the result of Kulkarni et al (26) who reported 10% infection rate after VPS insertion but less than the results of Kinasha et al (13) who reported 24.6% shunt related infection but overall in our elective neurosurgical procedures the incidence of shunt related infection is still accepted.…”
Section: Discussionmentioning
confidence: 46%
“…However, they also reported the absence of any staphylococci in any of their AIS infections, which was in contrast to other published reports. In a retrospective review, Sciubba et al reported a 2.4-fold diminished pediatric shunt infection percentage when changing from standard to impregnated catheters with a follow-up period of 6 months (14). A statistically significant diminution of 6.5% to 1.2% in infection rates has also been stated by Pattavilakom et al (16).…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, their clinical effectiveness in drastically reducing shunt infections in clinical practice is doubtful and there remains a reluctance to apply AIS catheters because of their increased price not unavoidably translating into obvious patient advantage (14,15). There have been several studies with varying conclusions reported in the literature.…”
Section: Discussionmentioning
confidence: 91%